(untitled) (Global Journals of Research in Engineering, 2022)
Hi-Tech/Software Technology parks are being developed in many countries to create an efficient work environment for knowledge based industrial development. Major aim of these technology parks is to attract foreign companies to set up operations and to transfer the indigenous technological capability for the development of the local industries. The aim of this work is to find out factors that influence technology park development and a suitable strategic framework for successful implementation of Hi-Tech (HTP) and Software Technology Park (STP) in Bangladesh. For this study Analytic Hierarchy Process is applied as a Multi-Criteria Decision-Making Method (MCDM) which is a technology assessment tool. The assessment has been conducted by considering infrastructure, strategic